PEMANFATAAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN PENGETAHUAN SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Erniwati La Abute; Hasna Koba'a; Sukmawati Sukmawati; Muhamad Yahya; Hasrat A Aimang (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The learning process will run well of course by using intermediary media that are in accordance with the material being taught. Aside from being an intermediary medium, it is also useful for overcoming the limitations of space and time, such as objects that are too large can be replaced with reality, images, or film frames. The purpose of this study in Utilizing Learning Media in Increasing Student Knowledge in Islamic Religious Education Lessons at MA DDI Midaarul Ulum Kilongan, is to find out the state of the learning media that is in MA DDI Midaarul Ulum Kilongan, as well as to find out the use of learning media in the process of increasing student knowledge .. The method in this study uses a qualitative approach and data collection using observation and interview techniques. The results of this study indicate that the use of learning media in increasing student knowledge in Islamic religious education subjects at MA DDI Midaarul Ulum Kilongan is very good, which in the use of this learning media can help educators convey the material being taught, so that the message conveyed clearer and learning can run smoothly, regularly and effectively. In learning Islamic Religious Education at MA DDI Midaarul Ulum Kilongan, the media that is popularly used is audio-visual media. Because using audio-visual media can attract students' attention so that it can make it easier to learn a lesson provided by educators.